Soil Erosion Assessment Using RUSLE Model and GIS in Juma Watershed, Southern Amazonas State - Duarte, Miqueias Lima [UNESP] (2021)
The spread of deforestation in the Amazon region is a cause for concern, seeing as the breakdown of soil-forest equilibrium provokes and possibly accelerates several processes, including superficial erosion. This process is one of the major causes of soil degradation worldwide. The Revised Universal Soil Loss Equation (RUSLE) is a well-established and widely applied indirect method used to estimate soil loss, generating information that helps the conservation and proper management of soil and subsiding the policies of land use and occupation. This study estimated the potential of loss by laminar erosion of soil in the area of the basin of the Juma river, located in the municipality of Apuí, in the Southern Amazonas State. The RUSLE method was used to estimate soil loss in conjunction with GIS techniques. The results showed a predominance of areas with a high Natural Potential (NP) for erosion (200 to 600 t.ha-1.y-1), occupying about 77.58% of the examined region, and indicated that this high index is related to the LS factor. In relation to Soil Loss (SL), it was observed that there is a predominance of small potential (0 to 10 t.ha-1.y-1), occurring in 72.96% of the area, and the highest indices of soil loss (> 120 t.ha-1.y-1) were observed only in places occupied by exposed soil or farming areas where there are no conservation practices associated with terrain slope in place, which reiterates the importance of the adoption of appropriate agricultural practices.